Analysis of Standard Expenditure in the Preparation of the 2023 Local Government Budget at Regional Financial Management Agency of Jakarta - Ibrahim, Hafiz; Lutfi, Achmad (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study analyses the application of the analysis of standards expenditure (ASB) in the preparation of the Regional Revenue and Expenditure Budget (APBD) for the 2023 Fiscal Year at BPKD DKI Jakarta Province. The research addresses the urgent need for effective and efficient budgeting in local governments, especially given current economic challenges and demands for transparent financial management. The main objective of this research is to evaluate the effectiveness and efficiency of budgeting and identify the factors that hinder its implementation. This study employs a post-positivism approach to understand the occurring phenomena and provide solutions to issues in the budget preparation. Apart from that, this research uses W. Dunn (2003) theory about evaluation. The author uses descriptive qualitative research methods. The triangulation data collection technique is by theory, qualitative interview and documentation. The findings are expected to significantly contribute to local government in achieving good governance and serve as a reference for future research in regional financial and asset administration